2019
DOI: 10.1159/000496297
|View full text |Cite
|
Sign up to set email alerts
|

A Double Inverted Flap Surgical Technique for the Treatment of Idiopathic Lamellar Macular Hole Associated with Atypical Epiretinal Membrane

Abstract: Objectives: To propose a new technique of a double inverted epiretinal membrane (ERM) and internal limiting membrane (ILM) flap (double flap group) for the treatment of idiopathic lamellar macular hole (LMH) with atypical ERM (AERM) and to compare surgical outcomes to those of the standard technique of ERM and ILM peeling of the fovea including LMH (control group). Methods: AERM was tomographically defined as a medium reflective thickened membrane above the retinal fiber layers without retinal traction signs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…Comparing these two surgical methods, the difference between them lies in the disposition of ERM and ILM. Instead of peeling the membrane, the new method double inverted the ERM and flapped the ILM [28,29]. This kind of surgery can preserve the LHEP and promote LHM recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these two surgical methods, the difference between them lies in the disposition of ERM and ILM. Instead of peeling the membrane, the new method double inverted the ERM and flapped the ILM [28,29]. This kind of surgery can preserve the LHEP and promote LHM recovery.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to those studies that enrolled eyes with LHEP, the authors were contacted to ascertain whether these cases could be classified as degenerative according to Govetto's study [3]. Author of three studies [2,5,9] confirmed that their cases with LHEP can be classified as degenerative. Degenerative LMHs were included in the degenerative LMH group.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Comparing with the regular surgery method, the main difference is about the disposition of ERM and ILM. Instead of peeling the membrane, in the new method, ERM was double inverted and ILM was apped [28,29]. This kind of surgery can retain LHEP and promote the recovery of LHM, and a study indicated that the development of LHEP might be a recovery progress of LMH [15].…”
Section: Discussionmentioning
confidence: 99%